Estudo comparativo entre a manutenção e a ressecção da gordura retropatelar na artroplastia total do joelho - Rodrigo Barreiros Vieira (2015)
INTRODUCTION: Total knee arthroplasty (TKA) is a procedure that results in excellent satisfaction ratings to restore, even partially, painless joint function. However, the unsatisfactory results negatively impact the lives of patients, and major cause of failure is related to complaints of the patellofemoral joint. Nevertheless, there are few studies with good evidence that evaluate the influence of fat pad on the results of this surgical procedure. OBJECTIVES: compare the clinical and functional outcome, surgical time and the placement of the tibial component in TKA with maintaining or resection of retropatellar fat pad. METHODS: The present prospective, randomized, double blind, with the participation of 40 patients, 22 underwent maintenance of retropatellar fat pad (MG) and 18 to resection (RG). Evaluations were made of the maximum degree of flexion, measuring the pain by visual analog pain scale (VAS), measurement of the Knee Society Score (KSS) and function of the knee, patellar height by Insall-Salvatti index preoperatively, first, sixth and twelfth postoperative month and also analyzed the duration of surgery and radiographic positioning of the tibial component. RESULTS: The mean values for the surgical time was 98.32 min. MG group and 96.78 min. the RG group (p = 0.892). The averages were 103.2 ° vs. 100 ° (p = 0.466) to the maximum degree of flexion, the patella to the height was 1.10 vs. 1.07 (p = 0.20), with knee KSS vs. 83.41 83.06 (p = 0.46), with functional KSS vs. 73.95 78.06 (p = 0.39), pain intensity by VAS with 2.41 vs. 1.56 (p = 0.19) and positioning the tibial component with the AP vs. 91.18 ° 91.17 ° and 94.86 ° vs. profile 94.56 °. None of the variables was observed statistical difference between the groups. CONCLUSION: there is no difference between the aspects evaluated when comparing patients undergoing maintenance or resection fat pad during total knee arthroplasty.